An observational, multigenerational platform for health systems and population health interventions to minimise intergenerational transmission of non-communicable diseases in India: the YUVAAN cohort study protocol - Vaman Khadilkar; Tarun Reddy Katapally; Jasmin Bhawra; Neha Kajale; Rubina Mandlik; Vivek Patwardhan; Demi Miriam; Dipali Ladkat; Chidvilas More; Ketan Gondhalekar; Anuradha Vaman Khadilkar (BMJ Public Health)
Introduction Non-communicable diseases (NCDs) pose a significant health burden in India, with preventable risk factors contributing to their prevalence. In rural populations, inequalities may be reinforced by health risks passed down through generations. Taking a life course perspective, this multigenerational cohort study aims to investigate behavioural, socioecological, and socioeconomic determinants of growth and NCD risk, as well as healthcare access and utilisation among preadolescents and their parents.Methods and analysis The study is being implemented by the Hirabai Cowasji Jehangir Medical Research Institute (HCJMRI) using a prospective, multigenerational cohort design to investigate NCD risk over 15 years. Data are being collected from 14 villages around Pune, Maharashtra, India. The target population is asymptomatic (ie, healthy) children aged 8–10 years and their parents. The study commenced on 13 September 2022. Participants (children and their parents) are being enrolled through household visits, and by arranging subsequent visits to the primary health facility of HCJMRI. After obtaining informed consent from participants (parents and their children), comprehensive data are being collected from both children and parents, including clinical, behavioural, healthcare access and utilisation, as well as socioeconomic determinants of health. Clinical assessments include anthropometric measurements, blood samples for a wide range of NCD indicators, bone health and muscle function. The long-term data analysis plan includes longitudinal modelling, time-series analyses, structural equation modelling, multilevel modelling and sex-based analyses to investigate growth trajectories and intergenerational patterns of health risks. As of November 2024, 1070 families from 14 villages have been enrolled (1264 preadolescents and 2140 parents). Given the double burden of malnutrition, with undernutrition and overweight/obesity coexisting among children and parents in India, the study findings will contribute to the development of focused interventions aimed at lowering NCDs, addressing the generational transmission of health risks, and improving health outcomes for rural communities.Ethics and dissemination Ethics approval was obtained from the institutional ethics committee, Ethics Committee Jehangir Clinical Development Centre, No: JCDC/BHR/24/047.Trial registration number NCT05603793.